Ascidians collected during the Madibenthos expedition in Martinique: 1—Phlebobranchia - Monniot, Françoise (Zootaxa, 2018)
The aim of the Madibenthos 2016 expedition was to establish an inventory of the benthic marine fauna around Martinique. All kinds of biota were collected with different devices down to 40m depth. Among a large amount of invertebrates the ascidians were varied and abundant. Their study will be made in several steps. The first group studied concerns the Order Phlebobranchia represented here by species already described from the Caribbean area; one of them was collected for only the second time. The variability of internal characters which are ordinarily considered as generic or specific is discussed here for the genera Ascidia and Phallusia.